2016
DOI: 10.1002/srin.201600107
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Intercritical Annealing on the Microstructure and Mechanical Properties of Ferritic–Martensitic Two‐Phase Steels

Abstract: Modified press‐hardening processes are very attractive for manufacturing safety‐relevant vehicle body parts from steels with martensitic–ferritic microstructures. In the process developed, the formation of the two‐phase microstructure and the hot sheet forming simultaneously occur subsequently to an intercritical annealing. By contrast, previously used process chains do not integrate setting of a multi‐phase microstructure within the forming step. In order to successfully combine the intercritical annealing wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 23 publications
0
10
0
1
Order By: Relevance
“…In fact, the volume change during quenching from the intercritical annealing range induces plastic deformation of adjacent ferrite grains, and therefore, creates a high density of unpinned dislocations in the vicinity of martensite. These martensite‐induced dislocations move at low stresses, creating low yield strengths, and interact to produce high rates of strain hardening . Among DP steels, DP3 shows higher initial n ‐values compared with DP1 while DP3* is even better than DP3.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the volume change during quenching from the intercritical annealing range induces plastic deformation of adjacent ferrite grains, and therefore, creates a high density of unpinned dislocations in the vicinity of martensite. These martensite‐induced dislocations move at low stresses, creating low yield strengths, and interact to produce high rates of strain hardening . Among DP steels, DP3 shows higher initial n ‐values compared with DP1 while DP3* is even better than DP3.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have systematically studied the effect of volume fraction of martensite on mechanical properties of DP steels . It has been also revealed that the strength increases and total elongation decreases by increasing the amount of martensite in steels with carbon contents between 0.05 and 0.4 wt% . However, the main focus has been on achieving DP steels with high strength and acceptable formability and there are few reports on the low carbon side.…”
Section: Introductionmentioning
confidence: 99%
“…Seiring berjalannya waktu, teknologi modifikasi struktur mikro makin berkembang melalui berbagai rute proses untuk memenuhi kebutuhan sifat mekanik yang beraneka ragam. Salah satu proses yang saat ini banyak digunakan yaitu pemanasan fasa-ganda [2][3][4][5][6][7][8][9][10][11][12] .…”
Section: Pendahuluanunclassified